Issues & challenges of applying Islamic banking in Zanzibar: a way forward - Mustafa, Mzee Mzee; Othman, Ahmad Azam (Penerbit Universiti Sultan Zainal Abidin (UNiSZA), 2020)
The operation of Islamic banking in Zanzibar started in 2011 to boost economic activities and meet the demand of its people. However, the introduction of Islamic banking was not followed by any legal amendment to suit the operation of Islamic banking in the country as per Islamic principles. This paper, therefore, examines different laws which governed the Islamic banking in Zanzibar to find how far they support the operation of Islamic banking. The findings of this paper revealed that some of the laws in Zanzibar contain provisions that do not support Islamic banking transactions. The methodology adopted in this paper is based on the content analysis of legislations, leading textbooks, and journal articles. The study used a comparative method to address the study in question. The study recommends amendment of some laws such as the Contract Decree, 1917 and Transfer of Property Decree, 1917, Stamp Duty Act 2017, and Value Added Tax Act, 1998 for improving the legal regime governing Islamic banking transactions in Zanzibar.